NILAI-NILAI ETIK DALAM PELAYANAN PUBLIK: Praktik pada Dinas Pendidikan di Kota Padangpanjang - Lanin, Dasman; Syamsir, Syamsir (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
The objective of this study is to describe the ethical values of public service among public service personnel at Department of Education in Padangpanjang City. This study uses a quantitative approach with the type of ex post-facto. Population in this consisted of 10,864 individuals of heads of household in two districts and 16 villages of Padangpanjang. Sample was taken in two stages, cluster sampling and proportional stratified random sampling. Data were collected through questionnaires and analyzed using a statistical percentage, mean, and other central tendency according to research interests. Results of this study indicated that the ethical values of public service among public service personnel at the Department of Education in Padangpanjang City has not been well implemented.Key words: ethical values, attitudes, public service, educational service